Building a Better Place: Utopianism and the Revision of Community in Toni Morrison’s Paradise - Verena Harz (Current Objectives of Postgraduate American Studies)
This article examines the role of utopianism in Toni Morrison’s 1997 novel Paradise“. It argues that, by juxtaposing the all-black town of Ruby with a group of women living in a nearby convent, Morrison revises traditional views of what constitutes the best type of community. She criticizes the idea of utopian perfection predicated on purity and exclusion and envisions an alternative community characterized by ongoing negotiation. Rejecting all utopian master narratives, Morrison projects a better place at a more human scale.